The Routledge handbook of philosophy of responsibility - Kiener, Maximilian (Routledge, 2024)
"Philosophical inquiry into the theory and practice of responsibility is a major and fast-growing area of study. It spans perennial philosophical, political, and legal questions about free will and agency as well as more recent, controversial topics such as coercion, ignorance, and responsibility for historical injustices. The Routledge Handbook of Philosophy of Responsibility is an outstanding survey and exploration of these issues and more. Comprised of forty-one chapters by an international team of contributors, the Handbook is divided into three clear parts - on the history, theory, and practice of responsibility - within which the following key areas are examined: responsibility and wrongdoing responsibility and determinism the scope of responsibility individuals and society the concepts of responsibility the conditions and challenges of responsibility being and holding responsible the ethics and politics of responsibility responsibility in the law. Including suggestions for further reading at the end of each chapter, The Routledge Handbook of Philosophy of Responsibility provides an extremely useful guide to the topic. It will be valuable reading for students and researchers in philosophy and applied ethics, as well as for those in related disciplines such as politics, law, and policymaking"--
OCLC-licensed vendor bibliographic record
Keywords: PHILOSOPHY / General; Responsibility / Philosophy